Directive and Broadband 4-seg SRR Metamaterial Antennas - Dawar, Parul; De, Asok; Raghava, N. S. (International Journal of Advanced Science and Technology, 2016)
In this paper, a design of novel Mu Negative Group (MNG) 4segment SRR based microstrip patch antenna optimized for bandwidth, directivity and front to back lobe ratio has been presented. The microstrip patch antenna is designed using Ansoft HFSS version 13. Results were compared with MATLAB programming based on CAD formulas using equivalent circuit analysis of patch antenna. Nicolson Ross Weir (NRW) method has been used to retrieve the material parameters from transmission and reflection coefficient. Following this, a metamaterial-based-microstrip patch antenna has been designed. The unique shape proposed in this paper, gives remarkable enhancement in bandwidth by 30GHz, directivity by 2% and front to back lobe ratio by 9% but at cost of reducing antenna gain.